2012
DOI: 10.5433/1679-0359.2012v33n6p2347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical syndromes of nervous distemper in dogs initially presented without conventional evidences of CDV infection

Abstract: Despite large vaccination practice, canine distemper virus (CDV) is yet an important infectious agent that leads to nervous disease in canine populations worldwide. Unfortunately, the clinical diagnosis of distemper encephalomyelitis is often difficult in cases presented without conventional evidences of CDV infection such as systemic signs and myoclonus. Therefore, the aim of this study was to evaluate the neurological deficits and the clinical syndromes of nervous distemper in dogs suffering from neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The rapid diagnosis of CD is essential to establish the prognosis and assist in the early therapeutic management of the disease, optimizing the chances of successful treatment (AMUDE et al, 2012). However, the clinical presentation is not always evident.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid diagnosis of CD is essential to establish the prognosis and assist in the early therapeutic management of the disease, optimizing the chances of successful treatment (AMUDE et al, 2012). However, the clinical presentation is not always evident.…”
Section: Resultsmentioning
confidence: 99%
“…The canine core vaccines protect dogs against canine parvovirus infection (CPV-2), canine distemper (CDV) and infectious canine hepatitis (CAdV-1) [ 33 , 34 , 38 ]. It has been shown that any dog can be infected regardless of age, and cases of core diseases are reported also in senior dogs [ 39 , 40 , 41 ]. For this reason, core vaccinations are considered the main tool to control these diseases.…”
Section: Introductionmentioning
confidence: 99%